Increased cerebral blood flow with increased amyloid burden in the preclinical phase of alzheimer's disease. Issue 2 (30th May 2019) - Fazlollahi, Amir; Calamante, Fernando; Liang, Xiaoyun; Bourgeat, Pierrick; Raniga, Parnesh; Dore, Vincent; Fripp, Jurgen; Ames, David; Masters, Colin L.; Rowe, Christopher C.; Connelly, Alan; Villemagne, Victor L.; et al.
Abstract : Background: Arterial spin labeling (ASL) is an emerging MRI technique for noninvasive measurement of cerebral blood flow (CBF) that has been used to show hemodynamic changes in the brains of people with Alzheimer's disease (AD). CBF changes have been measured using positron emission tomography (PET) across the AD spectrum, but ASL showed limited success in measuring CBF variations in the preclinical phase of AD, where amyloid β (Aβ) plaques accumulate in the decades prior to symptom onset. Purpose: To investigate the relationship between CBF measured by multiphase‐pseudocontinuous‐ASL (MP‐PCASL) and Aβ burden as measured by 11 C‐PiB PET imaging in a study of cognitively normal (CN) subjects age over 65. Study Type: Cross‐sectional. Population: Forty‐six CN subjects including 33 with low levels of Aβ burden and 13 with high levels of Aβ. Field Strength/Sequence: 3T/3D MP‐PCASL. Assessment: The MP‐PCASL method was chosen because it has a high signal‐to‐noise ratio. Furthermore, the data were analyzed using an efficient processing pipeline consisting of motion correction, ASL motion correction imprecision removal, temporal and spatial filtering, and partial volume effect correction. Statistical Tests: General Linear Model. Results: In CN subjects positive for Aβ burden ( n = 13), we observed a positive correlation between CBF and Aβ burden in the hippocampus, amygdala, caudate ( P  < 0.01), frontal, temporal, and insula ( P  < 0.05). Data Conclusion: To the best of our knowledge, this is the first study using MP‐PCASL in the study of AD, and the results suggest a potential compensatory hemodynamic mechanism that protects against pathology in the early stages of AD. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2020;51:505–513.